An immunochromatographic strip sensor for sildenafil and its analogues. Issue 41 (26th March 2019) - Wang, Zhongxing; Wu, Xiaoling; Liu, Liqiang; Xu, Liguang; Kuang, Hua; Xu, Chuanlai
Abstract : A novel Sild hapten was successfully synthesized and a sensitive anti-Sild mAb was produced based on this hapten. The immunochromatographic assay (ICA) allowed qualitative and quantitative detection of Sild and its analogues in food samples within 15 min. The ICA was successfully applied to real samples and showed a good correlation with ic-ELISA. Abstract : In this study, a new hapten of sildenafil (Sild) was successfully synthesized and a sensitive monoclonal antibody (mAb) against Sild was produced based on this new hapten. The subclass of the mAb was IgG2a, and the half-maximal inhibitory concentration (IC50 ) of the mAb was 0.53 ng mL −1 . Next, an immunochromatographic assay (ICA) was established for detecting Sild and its analogues in functional foods, where the visual detection limit (vLOD) and cut-off values were 0.5 and 20 μg kg −1, respectively. With the aid of a strip scan reader, the ICA can measure Sild with an LOD of 0.7 μg kg −1 and a line range of detection between 1.40 and 13.11 μg kg −1 . The whole test process takes only 15 min. Therefore, the ICA provides a useful tool for the on-site detection and rapid initial screening of Sild in functional food samples.